2013
DOI: 10.1371/journal.pone.0073978
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human T-Lymphotropic Virus Infection in Indigenous Women from the Peruvian Amazon

Abstract: BackgroundIn an earlier study, we detected an association between human T-cell lymphotropic virus (HTLV) infection and cervical human papillomavirus (HPV) in indigenous Amazonian Peruvian women of the Shipibo-Konibo ethnic group. As both HTLV and HPV can be transmitted sexually, we now report a population-based study examining the prevalence and risk factors for HTLV-1 and HTLV-2 infection in this population.MethodsBetween July and December 2010, we conducted a comprehensive screening for HTLV among Shipibo-Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
1
16
0
2
Order By: Relevance
“…Conversely, in a case-control study by Rouet et al , low educational level was identified to be a main risk factor for HTLV-1 infection among blood donors in French West Indies [ 19 ]. Furthermore, Blas et al demonstrated that low literacy was indeed an important risk factor for HTLV-1 infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in a case-control study by Rouet et al , low educational level was identified to be a main risk factor for HTLV-1 infection among blood donors in French West Indies [ 19 ]. Furthermore, Blas et al demonstrated that low literacy was indeed an important risk factor for HTLV-1 infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Blas et al . could not find a significant association between the infection and breastfeeding due to very high prevalence of breastfeeding in both HTLV-1 seropositive and seronegative individuals [ 20 ]. On the other hand, breastfeeding was reported as one of the important risk factors for HTLV-1infection among blood donors from Taiwan with an odds ratio of 4.4 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Venezuela, a high prevalence was found for HTLV-2, reaching 61% among Guahibo and Yaruro 83 , 84 , 106 , whereas in central and southern Bolivia, only HTLV-1 was detected among the Quechua and Aymara indigenous peoples, with a prevalence of 6.8% and 5.3%, respectively 51 . In the Peruvian Andes, Quechua and Aymara, the most populous indigenous groups in the region, also present solely HTLV-1, with prevalence rates from 1.6% to 2.82% 51 , 73 , 92 , 117 , whereas in the Amazon, the Peruvian Shipibo-Konibo notably carry both viruses, with high prevalence rates ranging from 1.43% to 5.9% 4 , 15 , 92 and 2.1% to 3.8% 4 , 15 for HTLV-1 and HTLV-2, respectively. A few cases of only HTLV-2 have also been reported in two other indigenous groups of the Peruvian Amazon 92 ( Table 1 ).…”
Section: Htlv In Indigenous Groups Of Other Countries Of the Americasmentioning
confidence: 99%
“…2 There are also additional threats to health in the region, with a significant burden of vector-borne diseases, such as malaria 9 and dengue, 10 other infectious diseases, such as tuberculosis, 11 diarrhea (with sporadic cholera outbreaks), 12 , 13 and retroviral infections, including human immunodeficiency virus 14 (HIV) and human T lymphotropic virus (HTLV). 15 , 16 …”
Section: Introductionmentioning
confidence: 99%